Conflict between the internal law of a religious association and the state law in the scope of manifesting religious beliefs - Krajczyński, Jan (Prawo Kanoniczne, 2023)
Legal restrictions imposed by numerous countries in the period of struggle with the SARS-Cov-2 virus have been in many cases an example of violations of religious freedom in the field of manifesting religious beliefs. The aforementioned restrictions aimed at the protection of public life and health, often contrary to the internal law of religious associations in the field of compulsory public worship, prompted the author of the study to present the legal principles that should be respected in the case of imposing restrictions aimed at the protection of safety, public order, health, morality, or the freedoms and rights of others. The author presents relevant de lege ferenda postulates which may contribute to increasing the degree of protection of freedom to manifest religious beliefs while keeping to the principle of highest care for the common good and fundamental rights of others.